2008
DOI: 10.1007/s10535-008-0118-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silicon on defense of wheat against oxidative stress under drought at different developmental stages

Abstract: The effects of silicon application before sowing on the drought-induced oxidative stress and antioxidant defense in wheat (Triticum aestivum L.) were investigated. Drought stress was applied by withholding watering till sampling at booting or filling stage. Application of Si increased the water potential of drought-stressed plants at filling stage, whereas it did not at booting stage. The superoxide dismutase (SOD) activity was inhibited and peroxidase (POD) activity was enhanced by drought at booting stage, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(110 citation statements)
references
References 26 publications
8
93
0
2
Order By: Relevance
“…In this present study, soil applied Si significantly increased the SOD and CAT activity. It indicated that the oxidative damage due to high temperature in late sown wheat was ameliorated by Si application due to the remarkable increase of SOD and CAT and decrease of H 2 O 2 content (Liang et al 1996;Gong et al 2008). Gong et al (2005) reported that application of Si on wheat under water stress conditions also enhanced the activities of SOD, CAT and reduced the activity of H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In this present study, soil applied Si significantly increased the SOD and CAT activity. It indicated that the oxidative damage due to high temperature in late sown wheat was ameliorated by Si application due to the remarkable increase of SOD and CAT and decrease of H 2 O 2 content (Liang et al 1996;Gong et al 2008). Gong et al (2005) reported that application of Si on wheat under water stress conditions also enhanced the activities of SOD, CAT and reduced the activity of H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The ameliorative effects were seen at the grain filling stage compared to the booting stage under field conditions (Gong et al, 2008). Si alleviated the oxidative stress and regulated the activities of antioxidant enzymes.…”
Section: Role Of Silicon In Stressesmentioning
confidence: 92%
“…Alleviates oxidative stress and regulates activities of antioxidant enzymes Gong et al (2008) 11) Wheat Sodium silicate (2.11 mmol.kg -1 ) Alleviation of oxidative damage of functional molecules and maintainance of many physiological processes Gong et al (2005) 12) Wheat Sodium silicate (7.14 mmol) Improves growth Gong et al (2003) Zhang et al (2013) 2) Pistachio Sodium silicate (2.73 mM Si.kg -1 soil) Si enhanced the photochemical efficiency, photosynthetic gas exchange and antioxidant defense capacity Habibi and Hajiboland (2013) …”
Section: Acknowlegementsmentioning
confidence: 99%
“…Addition of silicon also improved water status and increased dry mass of wheat plants in pots under drought (Gong et al,. 2005(Gong et al,. , 2008.…”
Section: Silicon Uptake and Accumulation In Plantsmentioning
confidence: 99%
“…Under severe stress, these physiological biochemical reactions showed positive correlations with the amount of silicon supply. Gong et al (2008) showed that the intensity of oxidative destruction tested by the concentration of thiobarbituric acid reactive substances (TBARs) in the leaves of wheat was increased by drought, and there was a smaller increase upon application of silicon. …”
mentioning
confidence: 99%